2013
DOI: 10.3109/08958378.2013.810679
|View full text |Cite
|
Sign up to set email alerts
|

Early induction of uncoupling protein-2 in pulmonary macrophages in hyperoxia-associated lung injury

Abstract: Induction of UCP2 is an early response to hyperoxia in pulmonary macrophages. The mechanism is post-transcriptional. UCP2 induction follows a transient rise in mitochondrial ROS generation. The subsequent falls in Δψm and mitochondrial O₂ⁱ⁻ support the notion that regulable UCP2 expression in macrophages acts to contain mitochondrial ROS generation. That, in turn, may limit inappropriate pro-inflammatory activation in HALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Thus, this family of proteins protects against oxidative stress (Patti and Corvera, 2010; Echtay et al, 2002; Andrews et al, 2008; Jastroch et al, 2010; Krauss et al, 2005). A study by Steer, Mann (Steer et al, 2013) showed a significant induction of Ucp2 in murine pulmonary alveolar macrophages following exposure to high concentrations of oxygen. Particularly, this increment in protein levels of Ucp2 occurs in response to a rise in mitochondrial ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this family of proteins protects against oxidative stress (Patti and Corvera, 2010; Echtay et al, 2002; Andrews et al, 2008; Jastroch et al, 2010; Krauss et al, 2005). A study by Steer, Mann (Steer et al, 2013) showed a significant induction of Ucp2 in murine pulmonary alveolar macrophages following exposure to high concentrations of oxygen. Particularly, this increment in protein levels of Ucp2 occurs in response to a rise in mitochondrial ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with a mitochondria‐specific antioxidant, mitoTEMPO, during early post‐natal hyperoxia protected against compromised alveolarization (Datta et al , ), which suggests that targeted antioxidant therapy could be used to prevent or treat BPD. Hyperoxic exposure induces UCP2 expression in pulmonary macrophages and enhanced UCP3 levels in skeletal muscles in mice (Flandin et al , ; Steer et al , ), which may be compensatory responses to increased oxidative stress and mtROS. Further studies are required to determine the role of UCP in the development of BPD using genetic manipulation approaches.…”
Section: Mitochondrial Dysfunction In Chronic Lung Diseasesmentioning
confidence: 99%
“…Both 60-min bursts of hyperbaric oxygen and three-hour treatments with high-flow nasal cannula were shown to be efficacious, increasing cerebral blood flow and decreasing lactate levels with no sign of pulmonary or cerebral damage in patients with severe TBI [ 83 ]. Murine hyperoxia has been shown to induce UCP2 within 60 min, perhaps in response to the sudden increase in ROS production, suggesting a mechanism for this protection in which UCP2 was not being transcribed anew but that existing UCP2 mRNA and glutathione-coupled UCP2 were being mobilized; indeed, UCP2 protein level was found to increase with a corresponding decrease in ΔΨ m while the amount of UCP2 mRNA did not change [ 84 ]. This result extends specifically to toxicity mediated by hyperactivity associated with seizure in a murine model and is postulated to be at the core of the preconditioning phenomenon of cerebral vascular injury protection [ 32 ].…”
Section: Pathophysiology Of Ucp2mentioning
confidence: 99%